A Mix-Methodological Assessment Of Community Pharmacists’ Perception Towards Online Health Information In Federal Territory Of Kuala Lumpur, Malaysia - Ong, See Wan (2018)
Internet has become a common tool used by both healthcare professionals and the public to acquire up-to-date health-related information to improve their knowledge. Most of the studies described the growth of use of Internet around physicians, but information scarcity is reported around community pharmacists (CPs). Hence, this research was proposed in order to have better understanding of the current and future implications of Internet use for health information among Malaysian CPs.